The Effect of Microwave Disinfection on the Dimensional Change of Acrylic Resins. - Ahmad M Hussen; Lamia T Rejab; Luay N Abbood (University of Mosul, College of Dentistry, 2008)
Aims: To evaluate the effect of the microwave disinfection on the dimensional changes of the heat-cured acrylic resin. Materials and Methods: Heat-cured acrylic resin was used in this study. Thirtytwo disk-shaped specimens with reference points were prepared to evaluate the linear dimensionalchanges of the heat-cured acrylic resin that sterilized by microwave irradiation and by chemicalsolutions chlorhexidine and sodium hypochlorite. The specimens were divided into four tested groups,eight specimens for each group. Group I as control group and other groups divided according to thesterilization method. The dimensional change was evaluated with an Electronic Digital Caliper. Meanvalues wear compared statistically with: One-way Analysis of Variance (ANOVA), followed byDuncan's Multiple Range Test to determine the significant different among the tested groups at(p≤0.05) level of significance. Results: They showed that there was a highly significant difference ofthe means values of the linear dimensional change among the four tested groups. Specimens sterilizedby microwave irradiation have a higher value than that sterilized by the chemical solutions.Conclusions: The results of this study appeared that sterilization by the microwave irradiation producea significant effect on the dimensional stability of the heat-cured acrylic resin, while sterilization bychemical solution produce no significant difference.